Legal Framework for The Establishment of a Local-Owned Banking Enterprise: Study in Batu City - Ria Casmi Arrsa; Anindita Purnama Ningtyas; Fransiska Ayulistya Sutanto (Jurnal IUS Kajian Hukum dan Keadilan, 2021)
The establishment of a Local-Owned Enterprises (BUMD) operating in the banking sector has a strategic role for the people and the Government of Batu City in order to improve the economic status, public service, and competitiveness in the financial sector, and is an attempt to increase the regionally generated revenue as mandated by Law Number 23 of 2014 and Government Regulation Number 54 Year 2017. However, with the regulatory space and authority it has so far, Batu City Government has not established the BUMD as intended. Moreover, this paper will explain sociological aspect and the choice for politic of law for the Batu City Government in the framework of BUMD establishment in banking sector. Based on these circumstances, this paper uses a normative juridical research method to see regional community needs for banking financial institution owned by the Batu City Government. Based on the provisions of the legislation, the Batu City Government in preparing the process of establishing a BUMD begins with the formation of a BUMD formation team consisting of elements of the relevant Regional Apparatus, and prepare a research of regional needs and the feasibility of business fields in the banking sector to ensure the next step is to prepare and compile Regional Regulations governing the establishment of BUMD and ratification of legal entities by a notary through the Legal Entity Administration System of the Ministry of Law and Human Rights. According to theory and authoritative regulations, the formation of BUMD may be carried out in the form of a Legal Entity for a Regional Corporation, while the banking enterprise activities may be in the form of People’s Credit Banks (BPR) or Sharia People’s Financing Banks (BPRS).